'Bound hand and foot and handed over to the caste Hindus': Ambedkar, untouchability and the politics of Partition. (January 2018) - Cháirez-Garza, Jesús Francisco
This article examines B. R. Ambedkar's dramatically shifting politics in the years prior to Partition. In 1940, he supported the creation of Pakistan. In 1946, he joined Winston Churchill in his demands to delay independence. Yet, in 1947, Ambedkar rejected Pakistan and joined the Nehru administration. Traditional narratives explain these changes as part of Ambedkar's political pragmatism. It is believed that such pragmatism, along with Gandhi's good faith, helped Ambedkar to secure a place in Nehru's Cabinet. In contrast, I argue that Ambedkar changed his attitude towards Congress due to the political transformations elicited by Partition. Ambedkar approached Congress as a last resort to maintain a political space for Dalits in independent India. This, however, was unsuccessful. Partition not only saw the birth of two countries but also virtually eliminated the histories of resistance of political minorities that did not fall under the Hindu–Muslim binary, such as Dalits. In the case of Ambedkar, his past as a critic of Gandhi and Congress was erased in favour of the more palatable image of him as the father of the constitution. This essay reconfigures our understanding of Partition by showing how the promise of Pakistan shaped the way we remember Ambedkar.